2015
DOI: 10.5430/ijh.v1n1p28
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dignity therapy model on stress, anxiety and depression of hemodialysis patients

Abstract: Aim: Dignity therapy is a novel therapeutic approach to the treatment of psychological problems in patients under maintenance hemodialysis. The aim of this study was to determine the effects of dignity therapy model on stress, anxiety and depression of patients under maintenance hemodialysis. Methods: In a randomised controlled trial conducted from December 2013 to March 2014 in one hemodialysis center in Iran, 42 patients under maintenance hemodialysis were randomly assigned into two groups (control and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Many researches confirmed the high prevalence rate of depression in patients with CRF as the most common psychiatric diagnoses due to many social problems or mental stresses, which are associated with high rates of morbidity and mortality. Joshwa et al stated that the depression prevalence among these patients is 72% in India, 12% of whom suffer from severe depression (22) and in Iran the prevalence is 79% (23). Depression symptoms in chronic dialysis patients are more prevalent than other chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Many researches confirmed the high prevalence rate of depression in patients with CRF as the most common psychiatric diagnoses due to many social problems or mental stresses, which are associated with high rates of morbidity and mortality. Joshwa et al stated that the depression prevalence among these patients is 72% in India, 12% of whom suffer from severe depression (22) and in Iran the prevalence is 79% (23). Depression symptoms in chronic dialysis patients are more prevalent than other chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…29 In medical environments and hospitals, dignity encompasses independence, honesty, justice, respect for human rights, awareness and active defence of the patient. 30 Preserving patient dignity in various hospital wards is crucial, and respecting rights related to individual dignity is a principle of work and professional ethics. Some studies have shown that hospital patients are susceptible to losing their human dignity.…”
Section: Discussionmentioning
confidence: 99%
“…Dignity is a fundamental concept in health systems and the focus of medical and nursing care 29 . In medical environments and hospitals, dignity encompasses independence, honesty, justice, respect for human rights, awareness and active defence of the patient 30 …”
Section: Discussionmentioning
confidence: 99%